KEPEMIMPINAN KLINIS DOKTER UMUM DI RUMAH SAKIT KANKER DHARMAIS - Ratna Budi Setiani; Andreasta Meliala; Rina Kusumaratna (Journal of Health Service Management, 2022)
Background: Dharmais Cancer Hospital is a special class A cancer hospital which is a reference for the National Cancer Center with multidisciplinary health workers. With the specialist role of the Dharmais Cancer Hospital, general practitioners are also involved in improving the quality of patient care. To encourage this, the clinical leadership skills of a general practitioner are also urgently needed. Objective: Assess the level of clinical leadership and explore individual and service factors that play a role in clinical leadership in General Practitioners at Dharmais Cancer Hospital. Methods: Case study research using quantitative and qualitative data approaches to all general practitioners who serve as doctors on duty at the Dharmais Cancer Hospital. Collecting data using a questionnaire using modified instruments from the Clinical Leadership Competency Framework-self-assessment tool, document review, interviews and observations. Quantitative data analysis with frequency distribution and qualitative data analysis with thematic analysis. Results: Quantitative data shows that the dimensions of service improvement are included in the standard category. Qualitative data shows aspects of clinical leadership that need to be improved, including 2 aspects on the dimension of showing self-quality, namely self-management and acting with integrity, 2 aspects on the dimension of working with others, namely encouraging contribution and working in teams, 1 aspect on the dimension of managing services, namely managing resources, and 2 aspects on the dimensions of improving services, namely encouraging improvement and innovation and facilitating change. The individual factors considered to play a role were the majority at a younger age, the majority of years of service were new, the employment status of the majority were non-PNS not permanent, no work experience, no managerial experience, lack of managerial training, and lack of leadership training. Service factors considered to play a role include poor service communication, work situations with high workloads, and unclear roles at work. Conclusion: General practitioners at the Dharmais Cancer Hospital do not yet have optimal clinical leadership, so management support is needed to improve the clinical leadership of general practitioners.